PENGARUH HEAT INPUT TERHADAP HASIL KEKUATAN SAMBUNGAN PENGELASAN SMAW PADA MATERIAL STAINLESS STEEL 201 - Valla Yuntan Fauzi Romdhoni; Fadelan Fadelan; Yoyok Winardi (Universitas Muhammadiyah Ponorogo, 2019)
This research aims to know the strength of the connection as well as welding heat input current in connection with welding method using the method exsperimen. This research using a variation on the current 40 A, 50 A and the A 60 with material using SMAW welding technique of stainless steel 201. The results obtained from the test data and test pull rockwel violence showed the presence of the influence of the use of violence against the current and voltage drop of the welding connection. The larger the flow used will be the bigger value is also violence and its voltage, but at 60 A stream of violence and its voltage decline. Rockwell hardness test results for the area of las who have the highest violence are contained in the current 50 A of 73.60 HRB and the lowest at 40 A with flow of 63.6 HRB. As for the pull-test results with the flow that gets the results of voltage drop on average the highest found in the current 50 A of 0.711 kN/mm 2 and to pull the average voltage low current is present on 60 A of 0.5199 kN/mm2.